(untitled) (Tempo e Argumento, 2022)
This article aims to analyze a set of cartoons published in Cadernos do Terceiro Mundo magazine between 1977 and 1979. The proposal is to make an introduction to the debate of the cartoon as a source and object for historical research, considering humor and irony as constitutive elements of cartoon for historical analyses and, from a magazine that had a circulation in several countries of Latin-American continent and with strong political character. As a case study, this article aims to analyze the approach of the cartoons of Cadernos on human rights policy of Jimmy Carter’s government (1977-1981) for Latin-American countries.